Congenital Sucrase-isomaltase Deficiency: A Novel Compound Heterozygous Mutation Causing Aberrant Protein Localization. Issue 5 (May 2017) - Haberman, Yael; Di Segni, Ayelet; Loberman-Nachum, Nurit; Barel, Ortal; Kunik, Vered; Eyal, Eran; Kol, Nitzan; Hout-Siloni, Goni; Kochavi, Brigitte; Avivi, Camila; Schvimer, Michael; Rechavi, Gideon; et al.
ABSTRACT: Objectives: Congenital diarrheal disorders is a group of inherited enteropathies presenting in early life and requiring parenteral nutrition. In most cases, genetics may be the key for precise diagnosis. We present an infant girl with chronic congenital diarrhea that resolved after introduction of fructose-based formula but had no identified mutation in the SLC5A1 gene. Using whole exome sequencing (WES) we identified other mutations that better dictated dietary adjustments. Methods: WES of the patient and her parents was performed. The analysis focused on recessive model including compound heterozygous mutations. Sanger sequencing was used to validate identified mutations and to screen the patient's newborn sister and grandparents. Expression and localization analysis were performed in the patient's duodenal biopsies using immunohistochemistry. Results: Using WES we identified a new compound heterozygote mutation in sucrase-isomaltase ( SI) gene; a maternal inherited known V577G mutation, and a novel paternal inherited C1531W mutation. Importantly, the newborn offspring carried similar compound heterozygous mutations. Computational predictions suggest that both mutations highly destabilize the protein. SI expression and localization studies determined that the mutated SI protein was not expressed on the brush border membrane in the patient's duodenal biopsies, verifying the diagnosis of congenital sucrase-isomaltase deficiency (CSID). Conclusions: The novel compound heterozygote V577G/C1531W SI mutations lead to lack of SI expression in the duodenal brush border, confirming the diagnosis of CSID. These cases of CSID extend the molecular spectrum of this condition, further directing a more adequate dietary intervention for the patient and newborn sibling. Abstract : Supplemental Digital Content is available in the text